Combined pulmonary fibrosis and emphysema in hypersensitivity pneumonitis. (21st December 2015) - Soumagne, Thibaud; Pana-Katatali, Héloïse; Degano, Bruno; Dalphin, Jean-Charles
Abstract : Combined pulmonary fibrosis and emphysema is a distinct syndrome reported in patients who smoke. A 72-year-old, never-smoking female dairy farmer was referred for progressive dyspnoea on exertion, basal crackles on auscultation, normal spirometry and normal lung volumes but decreased diffusing capacity of the lung for carbon monoxide, centrilobular emphysema in the upper zones of the lungs and diffuse infiltrative lung disease in the lower zones on high-resolution CT scan. Bronchoalveolar lavage differential cell count showed 35% lymphocytosis, and precipitating antibodies for Wallemia sebi, Trichoderma species and Cladosporium sphaerospermum were identified. The diagnosis of farmer's lung disease with combined pulmonary fibrosis and emphysema was retained. This case highlights for the first time that hypersensitivity pneumonitis should be suspected in the setting of combined pulmonary fibrosis and emphysema in non-smoking patients.